Efeitos da estimulação ultra-sônica sobre o processo de reparo em ferida de extração dental: estudo histológico em ratos. - Santos Júnior, P. V.; Melhado, R. M. (My University, 1990)
The effects of ultrasound on the wound healing process after teeth extractions were studied histologically. The right upper incisor was extracted in 56 rats. They were divided into 2 groups, one control (I) and one experimental (II). Group II received ultrasound stimulation that was applied with the frequency of repetition of 1,000 Hz and pulse length of 2,000 us continuously, during five minutes daily since the extraction day until 24 hours before the death. The rats were sacrificed at 3, 6, 9, 12, 15, 18, and 21 postoperative days. The results showed a precocious granulation tissue formation, faster remodeling of osseous ridges, and consequently acceleration of the alveolar wound healing process.
Effects of ultrasonic stimulation on tooth extraction wound healing: histological study in rats
Keywords: animal; bone regeneration; incisor; jaw; rat; rat strain; tooth extraction; ultrasound therapy; wound healing; Alveolar Process; Animal; Bone Regeneration; English Abstract; Incisor; Rats; Rats, Inbred Strains; Tooth Extraction; Ultrasonic Therapy; Wound Healing